RANCANG BANGUN TRAINER DENGAN LCD LAYAR SENTUH MENGGUNAKAN ARDUINO MEGA 2560 SEBAGAI MEDIA PEMBELAJARAN PADA MATA KULIAH ELEKTRONIKA DIGITAL - Fitri Nur, Rosita (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2020)
Abstract. This research type is Research and Development (R&D) that aimed to develop a trainer with LCD touch screen using Arduino Mega 2560 as a learning media in Digital Electronics subjects which consists of; 1) Potential and problems, 2) Data retrieval, 3) Product design, 4) Product validation, 5) Design revision, 6) Product trial, 7) Product trial, and 8)Usage Trial.. The object of this field is a trainer equipped with a digital electronics practicum module. The method that used in collecting data in this field was testing and observing the performance of trainer with LCD touch screen and testing conducted by giving questionnaires to 38 students of Electronics Engineering Education Study Program, Jakarta State University. The feasibility test of media learning was tested by material and media experts. The result of media development is a trainer with LCD touch screen which contains of 3 digital circuit modules, namely a logic gate module, a flip-flop module and a combinational circuit module. The results showed that the percentage of media feasibility was obtained 94.64% from material experts, 96.96% from media experts, and 84.5% from the results of trials on students. From this acquisition, this media learning is very feasible to be used as a media learning of Digital Electronics subject in Electronics Engineering Education study program at State University of Jakarta.